Kalanchoe sect. Streptanthae (Crassulaceae subfam. Kalanchooideae), a new two-species section in K. subg. Bryophyllum - Smith, Gideon F. (Phytotaxa, 2023)
A new section, Kalanchoe sect. Streptanthae, with two Malagasy species, K. streptantha and K. bogneri, the only ones included in it, is described in K. subg. Bryophyllum (Crassulaceae subfam. Kalanchooideae).